Properties of Cement-Solidified Soils for the Process Control Program - Jang, Junhyuk; Chang, Naon; Kim, Sung-Wook; Jung, Junyoung; Kim, Dong-Su (Archives of Metallurgy and Materials, 2026)
The performance of cement-solidified soil waste was evaluated following Process Control Program (PCP) guidelines. Illite-based soils were used as surrogate for radioactive soil waste. The optimal mixing ratio of water, cement, and waste was determined from compression strength and workability; the solidified block at a mixing ratio of 25 wt.% water, 50 wt.% soil, and 25 wt.% cement exhibited 12.7 MPa of compression strength with good workability. Cement-solidified soil blocks in PCP size (diameter: 100 mm; height: 200 mm) were fabricated at the determined mixing ratio. Compression, immersion, thermal cycling, and irradiation tests were performed on the solidified blocks. The cement-solidified blocks passed the acceptance KORAD criteria for disposal, satisfying a compression strength above 3.44 MPa after all tests. Leaching tests were performed by piking radioactive natural soils (39.36 Bq/g), showing no radioactivity. These results suggest that radioactive soil waste can be solidified with cement by following PCP guidelines.